2019
DOI: 10.1016/j.trac.2019.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical fluid chromatography – Mass spectrometry: Recent evolution and current trends

Abstract: • A detailed summary on SFC-MS interfaces is given, with emphasis on current issues and potential solutions. • Differences between LC-MS and SFC-MS in terms of matrix effects generated are highlighted. • Sensitivity under SFC-MS has been demonstrated to be comparable to what it can be reached in LC-MS conditions. • Applications for SFC-MS are shifting towards the analysis of compounds with increasing polarity and analytes available in complex matrices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(27 citation statements)
references
References 84 publications
0
27
0
Order By: Relevance
“…In fact, more selectivity could be gained thanks to the MS detector, which would allow having a specific response depending on the differences concerning mass/charge ratios of the analytes. Several studies have demonstrated that UHPSFC can be successfully coupled to MS detectors, and this chromatographic method can be easily transferred to MS detection by integrating it with an appropriate make‐up solution to promote analyte ionization (for instance, in ESI‐MS, MeOH/water 98/2% v/v with 0.1% of ammonium formate) 25 . However, some considerations must be made in this context.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, more selectivity could be gained thanks to the MS detector, which would allow having a specific response depending on the differences concerning mass/charge ratios of the analytes. Several studies have demonstrated that UHPSFC can be successfully coupled to MS detectors, and this chromatographic method can be easily transferred to MS detection by integrating it with an appropriate make‐up solution to promote analyte ionization (for instance, in ESI‐MS, MeOH/water 98/2% v/v with 0.1% of ammonium formate) 25 . However, some considerations must be made in this context.…”
Section: Resultsmentioning
confidence: 99%
“…24) Moreover, a packed column, filled with bare silica, which was developed as a stationary phase for HPLC, was shown to be applicable to SFC. 25) Upon supercritical carbon dioxide silica gel column chromatography, the chromatographic behaviors of hydrophobic compounds were similar to those on normal-phase HPLC. In addition, SFC gave a better separation of chiral compounds when compared with HPLC.…”
Section: Analytical Chemistry In Biology and Medicinementioning
confidence: 88%
“…Supercritical fluid chromatography (SFC) is an alternative technique for separation of chiral compounds and provides several advantages over HPLC. [12][13][14][15] The mobile phase contains a large fraction of carbon dioxide, which has lower viscosity and higher diffusivity than liquid chromatographic solvents. As a consequence, high flow rates can be used without loss of resolution or efficiency and shorter equilibration times are achieved.…”
Section: Several High Performance Liquid Chromatography (Hplc) Methodsmentioning
confidence: 99%